A apelação cível e seus efeitos devolutivo e suspensivo no código de processo civil de 1973 e no novo CPC - Ribeiro, Cristiana Zugno Pinto (2015)
The appeal has been, over the centuries, the paradigmatic recourse oriented to combat, par excellence, judicial decisions that resolve conflicts. Under Brazilian law and the current term of the 1973 Civil Procedure Code (“CPC”), the appeal is the appropriate recourse against any and all awards, requiring, for its suitability, only a party’s detriment. Its main effects are ‘devolutive’ and ‘suspensive’. The appeal has an extensive ‘devolutive’ effect, for it allows an analysis by the ad quem Court of both matters of fact and of law raised in the course of the proceedings, as well as the challenge of any defects in the ruling, being the main instrument through which the ‘double degree of jurisdiction principle’ is verified. The ‘suspensive’ effect is present as a general rule in the appeal, so that, save in exceptional cases provided for in art. 520 and sparse provisions of the 1973 CPC and disperse laws, the mere filing of the appeal prevents enforceability of an award. The Brazilian civil procedure is experiencing a moment of transition, taking into account the recent approval by Congress of a new Civil Procedure Code. Although the search for a timely and effective process is a goal of the new CPC, it does not appear that there are significant changes with respect to the main form of recourse in Brazilian civil procedure. In the new CPC, any award incites the filing of an appeal. The recourse remains with a wide ‘devolutive’ effect, allowing the challenge of any defects in the ruling, be it formal or material. And, after years of discussion in doctrine and in Congress regarding the need for the obliteration of the ope legis ‘suspensive’ effect of the appeal, in order to allow an immediate execution of the award, the new CPC upholds the 1973 CPC rule. In conclusion, the new CPC remains with the conservative idea of excessive protection of respondent’s rights in detriment of claimant’s. It can be understood that the new CPC, from the perspective of the appeal, does not exceed the 1973 CPC ideology and does not have the power to shift its paradigms.